Hubungan Penggunaan KB Hormonal Suntik dengan Usia Menopause - Febry Heldayasari Prabandari; Winda Yusinta Baunsele; Evy Ernawati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: Menopause is the end of the biological process of the menstrual cycle which occurs due to a decrease in the production of estrogen hormones produced by the ovaries. Menopause is also the beginning of the cessation of menstruation for 12 months which generally occurs at the age of 45 to 55 years. One of the factors that influence the occurrence of menopause is hormonal contraception. Objective: To determine the relationship between the use of injectable hormonal birth control and age at menopause at the Integrated Service Post Mawar. Method: This type of research is quantitative with an analytical observational design and cross sectional approach. The sample in this study was 52 respondents, the sampling technique used was total sampling and analyzed using the chi-square test. Results: The majority did not use hormonal birth control with a total of 28 respondents (53.8%) and a small portion used hormonal birth control with a total of 24 respondents (46.2%), and the majority of respondents had a menopausal age of > 55 years with a total of 30 respondents ( 57.7%) and a small proportion of respondents had a menopausal age of <45 years with a total of 22 respondents (42.3%). The chi-square test results show a p value of 0.000. Conclusion: There is a correlation between using of injectable hormonal contraception and menopause age. Implication: This finding illustrates that hormonal contraception has an impact on a woman's age of menopause, with the hope that it can be a basis for consideration for the government in designing new regulations regarding the use of contraception in women.